The ratio of the use of long and short forms of dative in the sixteenth century Lithuanian reformers’ writings - Dambrauskas, Kęstutis (Lietuvių kalba, 2017)
The morphological features of Old Lithuanian texts have been explored by numerous linguists, however, the archaic dative forms have received much less attention. The aim of this article is to discuss the ratio of the use of short and long forms of dative in the Catechism by Merkelis Petkevičiaus (PC) and the Jokūbas Morkūnas Postilla (MP). The data comes from the PC as well as from the first 100 pages of the MP’s Part I and Part III. The paper uses descriptive and comparative methods. The results show that short dative singular and plural forms dominate in the PC. Most of the long (archaic) dative forms were found in the MP’s Part III. The ratio of the use of the short and long forms of dative is similar in the MP’s Part I. The plural form of long dative is mostly used in the PC and the MP’s Part I. The ratio of the use of singular and plural dative forms is similar in the MP’s Part III. Dative singular short forms were more frequent than the long ones in the PC and the MP’s Part I. The latter long dative forms were similarly used in the MP’s Part III. Dative singular short forms with the ending -u are much more frequently used in the MP’s Part III than in the MP’s Part I and the PC. The results of the study confirm that the PC, the MP’s Part I and Part III were translated by different translators.